Synthesis of Photothermally Stable Triangular Silver Nanoplates for SERS Applications, Photokilling of Bacteria. Issue 1 (22nd November 2019) - Fan, Ranran; Yang, Yushan; Xue, Jin; Zhang, Fang; Sun, Jie; Xu, Hui; Jiang, Tingting
Abstract: We developed a facile seeded‐growth strategy to synthesize triangular silver nanoplates with enhanced photothermal stability, in which zwitterionic buffers, hydroquinone (HQ) served as shape‐directing, reducing agents, respectively. Compared to the Ag nanoplates synthesized by the thermal methods reported before, the Ag nanoplates prepared in this study still retained the sharp tips of nanoplates, maintained excellent near infra‐red (NIR) surface plasmon resonance (SPR) properties after repeated NIR irradiation. The enhanced photothermal stability could enable the as‐prepared Ag nanoplates serve as stable substrates for bacterial surface enhanced Raman scattering (SERS) applications. Meanwhile, the Ag nanoplates synthesized in this study also yielded a steady‐state photothermal conversion efficiency up to 40%, giving effective photothermal therapy (PTT) towards antibiotic resistant bacteria. Abstract : They can take the heat : A simple seeded‐growth strategy was used to synthesize triangular silver nanoplates with enhanced photothermal stability. HEPES, hydroqunione (HQ) serve as shape‐directing, reducing agents, respectively. The as‐prepared Ag nanoplates can be used as NIR absorbers for antimicrobial photothermal therapy (PTT), as stable substrates for near infra‐red (NIR) surface enhanced Raman scattering (SERS).